Commercial Production of Autologous Stem Cells and Their Therapeutic Potential for Liver Cirrhosis. Issue 3 (March 2017) - Lin, Yi-Chun; Harn, Horng-Jyh; Lin, Po-Cheng; Chuang, Ming-Hsi; Chen, Chun-Hung; Lin, Shinn-Zong; Chiou, Tzyy-Wen
Human adipose-derived stem cells (hADSCs) are a promising source of autologous stem cells for personalized cell-based therapies. Culture expansion of ADSCs provides an attractive opportunity for liver cirrhosis patients. However, safety and stability issues can pose big challenges for personalized autologous stem cell products. In the present study, we addressed whether the commercial production program could provide a consistent product for liver cirrhosis therapy. We collected adipose tissue from three human donors by lipoaspirate and isolated ADSCs, which were expanded in culture to reach 1 × 10 8 cells (an approximately 1, 000-fold expansion) within four passages. We then examined their morphology, chromosome stability, surface markers, and differentiation ability after culture. Next, we explored their therapeutic potential using a rat model of thioacetamide-induced liver cirrhosis. Culture-expanded ADSCs were injected intrahepatically, and their biodistribution was tracked by immunohistochemistry using an antibody against human mitochondria. Finally, we tested for tumor development by subcutaneously injecting a 100-fold dose range of cultured ADSCs into immunocompromised mice. Taken together, we find that culture expansion of autologous ADSCs is a potentially suitable stem cell product for personalized cell-based therapy for patients with liver cirrhosis.